Тонкоплівковий світлодіодний випромінюючій елемент на основі органічних сполук - Просяник, М. С. (ХНУРЕ, 2023)
An artificial lighting device based on a thin film structure using organic nanolayers, as well as diffraction microstructures for the redistribution of the light flux, is considered in the presented work. The modern ITO/HMTPD/TAZ:Ir(ppy)3-BCP/Alq3/Al structure was chosen for modeling and calculation of light and electrical characteristics. As a result of the performed modeling, the electrical and optical characteristics of the indicated LED were obtained, in particular, the volt-ampere characteristic, the light characteristic, the spatial distribution of radiation, the directional diagram of the device.